2019
DOI: 10.3390/ijerph16060906
|View full text |Cite
|
Sign up to set email alerts
|

Health Risks of Polybrominated Diphenyl Ethers (PBDEs) and Metals at Informal Electronic Waste Recycling Sites

Abstract: Concerns about the adverse public health consequences of informal electronic waste (e-waste) recycling are increasing. This study adopted a cross-sectional study design to gain insights into health risks (cancer and non-cancer risks) associated with exposure to e-waste chemicals among informal e-waste workers via three main routes: Dermal contact, ingestion, and inhalation. The e-waste chemicals (PBDE and metals) were measured in the dust and top soils at e-waste sites (burning, dismantling, and repair sites).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
48
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
2
2
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(51 citation statements)
references
References 42 publications
2
48
1
Order By: Relevance
“…Fang et al (2013) found high hazard index for workers in mechanical sorting and dismantling workshops caused by dust ingestion with Pb being the greatest contributor in both workshops (80% to 92% of hazard index). Ohajinwa et al (2019a) found negligible non-cancer risks around the e-recycling workshops, except for workers in the repair area where the hazard index was higher than one due to dust ingestion directly from e-waste.…”
Section: Non-carcinogenic Riskmentioning
confidence: 83%
See 4 more Smart Citations
“…Fang et al (2013) found high hazard index for workers in mechanical sorting and dismantling workshops caused by dust ingestion with Pb being the greatest contributor in both workshops (80% to 92% of hazard index). Ohajinwa et al (2019a) found negligible non-cancer risks around the e-recycling workshops, except for workers in the repair area where the hazard index was higher than one due to dust ingestion directly from e-waste.…”
Section: Non-carcinogenic Riskmentioning
confidence: 83%
“…When exposure to more than one substance is being assessed, the hazard quotients can be summed to calculate a hazard index, thus indicating the risk from multiple hazards (Ohajinwa et al, 2019a). As with the hazard quotients, if the hazard index is greater than one, the potential for non-cancer risk is significant, if it is less than one, then the non-cancer risk is considered non-significant (Cao et al, 2020).…”
Section: Non-carcinogenic Riskmentioning
confidence: 99%
See 3 more Smart Citations